ANTHELMINTIC EFFEICACY OF AZADIRACHTA INDICA (NEEM) AGAINST STRONGYLES IN GOATS - Dongre, Shweta; Das, G; Nath, S; Dixit, AK; Agrawal, V (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present study was carried out to evaluate the efficacy of crude neem (Azadirachta indica) leaf powder in goats naturally infected with strongyle infections. Based on faecal sample examination, 24 adult goats positive for strongyle infection with > 1000 EPG (egg per gram) were selected and grouped as I, II, III and IV with 6 animals in each group. Group I was treated with Closantel @10mg/ kg body weight and Groups II and III were treated with crude neem leaf powder @ 0.5 g and 1.0 g/kg. b.wt. respectively whereas group IV was kept as infected untreated control. Faecal samples from each animal were examined on day 0, 7, 15 and 30 post-treatment and EPG was determined. The result showed significant reduction (p<0.05) in EPG in Group I from day 7 and was maintained till day 30 and in Group III on day 15 post-treatment but there was no significant variation in term of EPG in control group. Thus, it can be concluded that crude neem leaf powder has anthelmintic property.